Enhancing Energy Efficiency and Mitigating Environmental Degradation through Anaerobic Co-digestion of Palm Oil Mill Effluent and Solid Residues - O. Ajayi; A. P. Olalusi; O. O. Olarenwaju; I. H. Ifijen; A. D. Olugbemide (Journal of Applied Sciences and Environmental Management, 2024)
The utilization of palm oil mill residues for sustainable biogas production presents a promising avenue to mitigate environmental challenges associated with waste disposal and energy demand in palm oil processing. The study explores the use of palm oil mill residues for sustainable biogas production, focusing on the impact of mixing ratios of POME and three raw milled residues on biogas yield through anaerobic co-digestion. Results indicate that co-digestion significantly enhanced biogas production compared to mono-digestion of POME alone. The highest biogas yield of 370 ml was recorded in the digester with 40% residues followed by 50% with a cumulative biogas of 190 ml. The two digesters were higher than 80 ml recorded for POME alone.The findings underscore the potential of integrating palm oil mill residues into biogas systems to achieve dual objectives of waste management and renewable energy generation.